2017
DOI: 10.1038/s41598-017-10362-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen increases resilience to stress in mice

Abstract: The inability to successfully adapt to stress produces pathological changes that can lead to depression. Molecular hydrogen has anti-oxidative and anti-inflammatory activities and neuroprotective effects. However, the potential role of molecular hydrogen in stress-related disorders is still poorly understood. The present study aims to investigate the effects of hydrogen gas on resilience to stress in mice. The results showed that repeated inhalation of hydrogen-oxygen mixed gas [67%:33% (V/V)] significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
1
28
0
1
Order By: Relevance
“…Forced Swimming Test Forced swim test (FST) was modified from our previous reports. 21,31) A 20 cm diam-eter×35 cm high plastic cylinder was filled to a depth of 20 cm water (23-25°C). Mice were introduced into the water for a 6-min test session.…”
Section: Open Field Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced Swimming Test Forced swim test (FST) was modified from our previous reports. 21,31) A 20 cm diam-eter×35 cm high plastic cylinder was filled to a depth of 20 cm water (23-25°C). Mice were introduced into the water for a 6-min test session.…”
Section: Open Field Testmentioning
confidence: 99%
“…Tail Suspension Test Tail suspension test (TST) was performed following the existing protocol. 31,32) Mice were fixed by adhesive tape placed approximately 1 cm from the tip of the tail and were suspended 50 cm above the floor for a 6-min test session. The total time spent immobile in the last 4 min was recorded to reflect the depressive-like behavior.…”
Section: Open Field Testmentioning
confidence: 99%
“…Interestingly, some researchers also found that H 2 -rich water has neuron effects owing to its antioxidant properties. Although the deep mechanism is not clear, more and more researchers made an effort to study the biological function of H 2 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. To date, almost all H 2 gas production processes in the industry are based on natural gas, coal, petroleum, or water electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogen can readily permeate through biomembranes such as the blood-brain barrier, blood-testis barrier and placental barrier, thus benefiting hard-to-reach organs (e.g., brain) and organelles due to its low molecular mass, non-ionic state and hydrophobic properties. An increasing number of studies report that molecular hydrogen offers important neuroprotective benefits in depression, anxiety, neuropathic pain, Parkinson’s disease, cognitive impairment and brain injury via attenuating excessive inflammatory response and oxidative stress (Imai et al, 2016 ; Zhang et al, 2016 ; Gao et al, 2017 ; Iketani and Ohsawa, 2017 ; Wen et al, 2017 ). In mice, HRW consumption ad libitum prevented cognitive impairment with an associated suppression of the markers of oxidative stress, malondialdehyde and 4-hydroxy-2-nonenal, and reversed the suppression on neural proliferation of the hippocampus caused by chronic physical restraint (Nagata et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, in CMS-treated mice (chronic mild stress) HRW exerted antidepressant-like effects by preventing oxidative stress, inflammation and apoptosis in the prefrontal cortex and hippocampus. Inhalation of molecular hydrogen could enhance resilience to acute and chronic stress in mice (Zhang et al, 2016 ; Gao et al, 2017 ). These results strongly suggest that molecular hydrogen administration may be a novel medical approach for many types of diseases, specifically those related to the central nervous system (Ohno et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%